Determining the sustainability of a model of PBL: A Conceptual framework - Penelope Little; Margaret McMillan (Halla Newcastle Education and Research Center, 2016)
Objectives: To explore processes of implementation that result from attempts at curriculum renewal reliant on principles of PBL in a delivery model. Methods: An evaluation design using case study was chosen to appraise the worth of curricula reliant on PBL philosophy and methodology. The method involved actual stories or narratives depicting situations and experiences of curriculum implementation. Results: The use of narratives illuminated daily challenges of students, staff members and other stakeholders and posed solutions to issues raised in a collaborative way. Conclusions: An evaluation process reliant on a collection of stories of the experiences of those involved shed some light on the perspectives of a range of stakeholders and tested the feasibility and practicality of curriculum design and implementation. There were three major areas on which academic colleagues needed to focus: Resources- PBL is no different from other approaches to curriculum development; implementation strategies need to comply with the existing institutional policies and work within existing resources and budget allocations. Processes- PBL strategies can be used in conjunction with flexible/ e-learning delivery modes that increase the potential use of a range of support materials to enhance cases as learning stimuli. Facilitator guides ensure consistency across groups. Results- Data on the effectiveness of the learning experience is regularly and routinely collected and fed back into continuous quality improvement.